The Impact of Curriculum Change on Students’ Learning Motivation - Miftahul Jannah; Nuzulul Isna (LPPM Institut Studi Islam Sunan Doe, 2024)
The background of this research was at the beginning of changing the teacher's curriculum as educators who had not been able to implement the new curriculum as a whole, so they were required to change the new curriculum from 2013 to the independent learning curriculum. This study aims to determine the impact of changing the educational curriculum on the learning motivation of students at SMPN 1 Jeumpa and SMPN 1 Blangpidie. The method used in this study uses descriptive methods by way of semi-structured interviews. The results of the study stated that the Independent Curriculum in the two schools was implemented quite well. Some schools are still designing the right formula for implementing the Independent Curriculum. Based on this description, the implementation of the Independent Curriculum after being analyzed is better and follows the educational culture. However, several things must be considered by policymakers and education implementers, so that the Independent Curriculum can be implemented properly and perfect the 2013 Curriculum in education at SMPN in Southwest Aceh.